Different pH Optima in the Two Steps of an Indirect Fluorescent Antibody Reaction for Clostridium botulinum Type E - Robohm, Richard A. (1974)
Quantitative measurements of the effects of ions on fluorescent antibody reactions have not been reported in the literature. Data in this report show the effects of ranges of H(+), phosphate, Mg(2+), and Ca(2+) molarities on antigen-antibody coupling during an indirect fluorescent antibody (IFA) reaction for Clostridium botulinum type E. These effects were quantified in two ways: (i) by microphotometric measurement of cell fluorescence intensity; and (ii) by visual estimation of cell fluorescence intensity on long glass strips treated with antibody in ion gradients. Optimal pH for the first part of the reaction (coupling of rabbit antibody to cells) was 7.25, and optimum in the second part (coupling of tracer globulin to the rabbit globulin) was pH 7.37. Running the reaction as little as 0.10 to 0.15 pH units off from the optima considerably reduced fluorescence intensity. Sodium phosphate buffer up to 0.1 M did not significantly affect either portion of the reaction. Ca(2+) and Mg(2+) showed no effect on the first part of the reaction. These results support the use of higher-strength phosphate buffer and indicate for the first time that IFA reactions may have two independent, narrow pH optima.